Updating and validating seagrass ecosystem knowledge in the gulf of California: a comprehensive review - Ramírez-Zúñiga, Magali Alejandra; Pérez-Estrada, Claudia Jeannette; López-Calderón, Jorge Manuel; Cannon, Abigail Libbin; Vanderplank, Sula; Favoretto, Fabio (Frontiers in Marine Science, 2024)
Seagrasses are globally acknowledged as crucial habitats as they provide a variety of ecosystem services. Mexico’s legislation protects most of these marine plants; however, the protection often fails in application. The Gulf of California, despite being a biodiversity hotspot, has scant data on seagrasses. Here, human activity and climate change increasingly threaten these coastal ecosystems, with conservation and research efforts lacking coordination at a regional level. Our manuscript aimed to review and standardize existing data on Gulf of California seagrass species, ensuring open access for data updates; pinpointing conservation deficiencies; and guiding future research. We have added new records to the official public data, but we were able to recapture only 25% of the seagrass locations meaning a potential reduction in their historical distribution of 45.8%. Even though Mexico’s legislation protects some species of seagrasses, it protection often fails in the application. We identified that only 6.1% of the seagrass locations are within protected areas that recognize their presence in their management plans (e.g., the Balandra Flora and Fauna Protected Area and the Upper Gulf of California and Colorado River Delta Biosphere Reserve). At least 55.9% of seagrass records are associated with potentially damaging activities like pollution, coastal modification or biological resources use, while 23% are exposed to higher frequency of marine heatwaves. Given the importance of seagrass meadows under Mexican law and their internationally recognized ecological value, sharing current information and guiding research is essential. Our study seeks to galvanize renewed research initiatives and raise more awareness on the conservation of the Gulf of California’s seagrasses.